Development of residual strains and their relaxation processes in atomically thin layers of core-shell structured nanoparticles - Park, Jun-Hyoung; Kim, Sung-Hoon; Yu, Taekyung; Ahn, Jae-Pyoung; Lee, Jae-Chul (ELSEVIER SCIENCE INC, 2021)
Residual elastic strains imposed on atomically thin films coated onto substrate materials cause changes in the electronic structures of such films. This knowledge has been employed in various industrial sectors as a means of tuning the optical, electrical, magnetic, and chemical properties of materials. Although the magnitudes of residual strains and properties of materials are closely related to the thickness of coating layers, the measurement of residual strains that develop in atomically thin films is challenging owing to the experimental complexities of conventional measurement methods. In this work, the residual strains developed in atomically thin Au overlayers grown epitaxially on Pd nanoparticles were measured using transmission electron microscopy based on nanobeam precession electron diffraction. Experiments revealed that a 1-nm-thick Au film can withstand an exceptionally high compressive strain of 4.3%, which is reduced to nearly zero as the film thickness increases beyond 5 nm. The microstructural evolution of Au films was monitored using high-resolution transmission electron microscopy and the large strain storage capacity and plastic relaxation behavior of Au films were interpreted by comparing them with the previous computer simulations and theoretical models.